Identification of the epidermolysis bullosa acquisita antigen by LH 7.2 monoclonal antibody: use in diagnosis. - Tatnall, F; Whitehead, P; Black, M; Wojnarowska, F; Leigh, I (1989)
The sera from two patients with epidermolysis bullosa acquisita were blotted against dermal extracts in comparison with the mouse monoclonal antibody LH 7.2. This antibody reacts with carboxy terminal region of type VII collagen. The epidermolysis bullosa acquisita antisera showed binding to the same molecular weight protein as LH 7.2 confirming that the target antigen for epidermolysis bullosa acquisita antibodies is the carboxy terminal region of type VII collagen. This newly described collagen forms the major component of anchoring fibrils. These findings are consistent with established ultrastructural data which have shown that the epidermolysis bullosa acquisita antigen is located within and below the lamina densa. The monoclonal antibody LH 7.2 provides an internal standard for epidermolysis bullosa acquisita autoantisera activity. The use of immunoblotting of epidermolysis bullosa autoantisera in comparison with the monoclonal antibody LH 7.2 provides definitive investigation for the diagnosis of this disorder.